On Editing. (3rd July 2019) - Maguire, Laurie; Smith, Emma
ABSTRACT: Covering the changes in Shakespeare editorial theory and practice over the decades between the publication of the Oxford Shakespeare (1986) and the New Oxford Shakespeare (2016), this article surveys a range of modern texts with different rationales and aimed at different readerships. The article has three sections: the imagery associated with editorial activity, issues of authorship and collaboration, and the place of performance in editions. We trace the conceptual changes between the Textual Companion that accompanied the 1986 edition, and the Authorship Companion that is the equivalent for the 2016 edition, discussing the role of quantitative and qualitative approaches to questions of authorship and collaboration. We pay particular attention to the metaphors and tropes that shape editorial discourse, finding their echoes in early modern paratextual material. Pervasive anthropomorphic textual imagery tends implicitly to feminize texts (and masculinize editors), and we discuss the changing demands on editors and the continued dominance of male editors, particularly for Shakespeare's tragedies and histories. A final section discusses Arden editorial generations of Hamlet alongside the play's own telos of interrupted succession and its preoccupation with ghosts and the past.